From Sketch to Museum - Drawing and sociomuseological practice (Cadernos de Sociomuseologia, 2025)
This study analyses «urban sketching» as a contemporary artistic practice that transcends visual representation and explores its possible relationship with museum practice. It observes the widespread devaluation of the use of graphic record by members of a model community and as a disused auxiliary practice in the fields of ethnography and anthropology. The aim is to investigate how sketching can become a means of enhancing the record of a community's memories, through a quantitative and comparative analysis of its collection.The study is based on a bibliographical review and critical analysis of sources that address the historical evolution of sketching and open up space for its intersection with the new interdisciplinary museology. Despite the fact that little use is made in museological practice of the memorial records of community members themselves, these may suggest surprising paths between museums and semiotics, the theory of social representations and social psychology. Sketching not only allows for individual and collective creative introspection, but also rescues artistic freedom and democratises individual expression, and might become a heritage museum object of relevant importance in both cultural and social spectrum. Keywords: Sociomuseology; Drawing; SocioExpography; Alentejo; Ethnography